Peripheral criminal injustice: how international support for criminal procedure reform in Ecuador worsened an already weak penal system - García-Guerrero, Jorge Eduardo (Criminological encounters, 2021)
This article explores the complex outcomes of the latest reform of the criminal procedure in Ecuador. The study shows how US-led interventions resulted in massive incarceration while the underlying procedures are systematically ignoring the Right to Due Process. As of today, the Ecuadorian judiciary appears to work more efficiently, while law enforcement remains highly selective and the penal system remains weak with regard to judicial independence, fair trial and the quality of its reasoning. Still, the police control what is considered as delinquency. Law enforcement is directed selectively to petty offences while systematically producing impunity for severe offences. Thus, and maybe counterintuitively, the Americanisation of Law and the introduction of the adversarial system deepened the weaknesses of Ecuador's criminal justice system. Our findings are of particular interest both to legal scholars and practitioners working for international aid agencies as they shed light on complex correlations that have yet not been studied in detail.